1997
DOI: 10.3801/iafss.fss.5-901
|View full text |Cite
|
Sign up to set email alerts
|

Fire Extinguishing Effect Of Mixed Agents Of Halon 1301 And Inert Gases

Abstract: Multiplier effect of mixed agents of trifluorobromomethane (halon 1301) and inert gases on flame extinction has been investigated, for the purpose of minimizing the use of halons. The inert gases examined are argon, nitrogen and carbon dioxide. The fire-extinguishing efficiency was determined by flame-extinguishing concentrations for n-heptane measured with a cupburner. An additive-property equation was derived by thermodynamic considerations to predict the fire-extinguishng efficiency of mixed agents and used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
1
4
0
2
Order By: Relevance
“…As can be seen from the results of the experiment, the action of BANM on the kinetic and diffusion flame does not lead to its strong and sharp cooling and the maximum reduction in temperature was around 230 о С, but the flame was not suppressed. Thus, the action of BANM probably leads to a decrease in heat formation due to the dilution of the atmosphere with nitrogen and agrees well with the results of the authors [29], where they also indicated the reduction in temperature as a result of the influence of the mixture of chladone and carbon dioxide on the hydrocarbon flame. Further increase in the concentration of aerosol and nitrogen leads first to a sharp decrease in temperature, but it is reduced further for 30-40 seconds from taking the burner to the flame, then it stabilizes.…”
Section: Discussion Of the Results Of The Study Of The Influence Of Nsupporting
confidence: 91%
“…As can be seen from the results of the experiment, the action of BANM on the kinetic and diffusion flame does not lead to its strong and sharp cooling and the maximum reduction in temperature was around 230 о С, but the flame was not suppressed. Thus, the action of BANM probably leads to a decrease in heat formation due to the dilution of the atmosphere with nitrogen and agrees well with the results of the authors [29], where they also indicated the reduction in temperature as a result of the influence of the mixture of chladone and carbon dioxide on the hydrocarbon flame. Further increase in the concentration of aerosol and nitrogen leads first to a sharp decrease in temperature, but it is reduced further for 30-40 seconds from taking the burner to the flame, then it stabilizes.…”
Section: Discussion Of the Results Of The Study Of The Influence Of Nsupporting
confidence: 91%
“…Аналіз загальних закономірностей процесів інгібування показує, що підвищити ефек-тивність інгібувальних засобів можна знизивши вміст окислювача в горючій суміші або в зоні горіння. Відповідно, робить висновок автор [13], газові флег-матизатори, додатково розбавляють, знижують кон-центрацію кисню в горючій системі і тим самим різко підвищують ефективність вогнегасної дії інгібітора. Автори [14] також вказують, що додавання азоту приводить до зменшення в 2,5 рази вогнегасної кон-центрації хладону 114В2 при гасінні н-гептану.…”
Section: літературний оглядunclassified
“…However, halon is considered the main factor in ozone depletion; hence, it was banned by the Montreal protocol. As a result, many studies have been conducted to replace halogen agents, and inert gases such as argon, nitrogen, and carbon dioxide are now used [1][2][3][4]. Figure 1 shows the schematic diagram of the gaseous fire-suppression system, which consists largely of storage, operator, controller, valves, pipe, and nozzle.…”
Section: Introductionmentioning
confidence: 99%